Preference, Perception, and Acceptability of Fluid Gels as a Potential Age-Appropriate Dosage Form for Elderly Patients with Dysphagia - Zul Hadif Abd Aziz; Haliza Katas; Marhanis Salihah Omar; Noraida Mohamed Shah; Salma Mohamad Yusop; Mohamad Nasir Shafiee; Siti Fatimah Mohd Tarmizi (Gels, 2022)
The development of pharmaceutical dosage forms that are tailored to specific populations according to their preferences and acceptability could improve medication adherence, which could lead to effective pharmacotherapy. This study evaluated the preference for and perceptions of fluid gels as a potential age-appropriate dosage form for older adults with dysphagia. The palatability and swallowability of the developed fluid gels were also assessed to determine the consumer acceptability of this formulation. A cross-sectional survey was conducted through the electronic distribution of a self-administered questionnaire among adults in Malaysia between April and December 2021. A randomized and double-blinded clinical study was conducted to evaluate the palatability and swallowability of the fluid gels in 30 healthy participants. A cross-sectional study involving 673 respondents revealed that the fluid gels were perceived positively by consumers (64.4%), were easily swallowed (50.8%), were safe to be consumed (45.3%), and were suitable as a new pharmaceutical formulation (43.8%). The clinical study shows that moderately thickened fluid gels masked the bitterness of the medication and were easily swallowed. The newly developed fluid gels were also positively perceived by the participants. Taken together, fluid gels have shown great potential as an innovative oral formulation that is suitable for consumption by elderly patients with dysphagia.